Macrolgae as an indicator of the environmental health of the Pirangi reefs, Rio Grande do Norte, Brazil - Azevedo,Carolina A. A. (2011)
The coral reefs of Pirangi beach have suffered the impact of anthropic actions, mainly those related to tourism. To evaluate these effects, algal samples were collected at nine stations, distributed along the reef fringe. The macrobenthic community (algae/coral) was identified through photographic methods. A total of thirty species of algae, five species of coral, and one species of mollusk were identified. In areas of intense tourist activity, small algae were predominant, while in areas without human interference, foliose algae were predominant. Cluster analysis of the organisms revealed a pattern in spatial distribution into five zones: (1) a submerged zone with very diverse flora, (2) a zone with a predominance of Caulerpa racemosa, (3) a zone with high coverage of Sargassum vulgare, (4) a trampled zone with bare spaces, small algae and Zoanthus sociatus, and (5) a zone with predominance of Palythoa caribaeroum. The results show that human disturbances of the natural order can result in a different distribution model for benthic organisms in reefs. Moreover, these results allow us to infer that the area studied has undergone changes resulting from human activities and that the differences in biological composition can be used as an important indicator of the health of the Pirangi reef.